DNA mtCOI Barcodes for Maritime Biosecurity: A Proof of Concept in French Polynesia Ports - Garcia-Vazquez, Eva; Ardura, Alba; Planes, Serge (Frontiers in Ecology and Evolution, 2020)
DNA barcodes have been proposed for diverse applications as markers for species identification. One application is not fully explored yet is their use for assessing the species biodiversity and presence of invasive alien species in maritime biosecurity. The phylogeographical signals of mtCOI gene have been sometimes used for inferring the number of introduction hits and the origin of biological invasions. Here we employed mtCOI barcodes of mollusks and acorn barnacles (N=751) from ports of the Windward Island of French Polynesia to infer the effect of port size, maritime traffic and degree of openness in the risk of biological invasions. With 17.2% of non-indigenous species recorded here, significant differences in diversity were found among docks, and between long-time docked ships and their closest piers. A higher proportion of non-indigenous species (NIS) was found from sheltered compared to open ports, regardless their size and traffic. Less frequent wave washing, lower effect of currents and partial isolation in sheltered ports could explain the difference. The results suggest that port biota surveys should focus first on ports sheltered from open sea and emphasize the value of mtCOI barcodes for early detection of potential invasive species, for prioritizing surveillance efforts.